2018
DOI: 10.2131/jts.43.223
|View full text |Cite
|
Sign up to set email alerts
|

Zonation of the drug-metabolizing enzyme cytochrome P450 3A in infant mice begins in pre-weaning period

Abstract: The drug-metabolizing enzyme CYP3A is a heterogeneous enzyme found in the liver that displays local characteristics referred to as "zonation." Zonation contributes to improved energy efficiency in metabolism. The objective of this study was to determine a scientific basis for the safety of fetuses and nursing infants in cases in which the use of pharmaceuticals by pregnant and nursing mothers is unavoidable. In addition, we analyzed CYP3A zonation in the liver using mice from the fetus stage to the nursing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For instance, necrosis causing cell mass loss may be responsible for the decrease of P450 expression. In AILI, necrosis mainly happened around a central vein area of the liver, where P450s are primarily expressed (Kietzmann, 2017;Kitaoka et al, 2018). Further immunostaining experiment may be required to test the zonation changes of P450s with APAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, necrosis causing cell mass loss may be responsible for the decrease of P450 expression. In AILI, necrosis mainly happened around a central vein area of the liver, where P450s are primarily expressed (Kietzmann, 2017;Kitaoka et al, 2018). Further immunostaining experiment may be required to test the zonation changes of P450s with APAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The CBD levels of the fetal brain were similar to those of other organs. We also report that the CYP3A family involved in CBD metabolism is rarely expressed in the fetal liver during this period (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, we felt the need to measure CBD levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning metabolism, CBD is oxidized in the adult liver by cytochrome P450 (CYP) 3A at the 6β, 2′, and 4′ positions (Jiang et al, 2011;Ujvary and Hanus, 2016). However, the metabolic activity of CYP3A is significantly lower in the fetal liver than in the adult liver (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, it is considered that CBD is distributed throughout the entire fetal body with little metabolism in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult liver, many drug‐metabolizing enzymes, including CYPs, are strongly expressed around the central vein (CV) and rarely around the portal vein. This characteristic expression pattern is called zonation structure and contributes to the efficient metabolism of drugs (Annunziato & Tchorz, 2021; Kitaoka, Hatogai, Ochiai, & Sugiyama, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although many studies have been reported on CYPs in the liver, they have focused only on the expression levels of CYPs, and there is little information on their relationship to zonation formation, which affects metabolic efficiency (Kitaoka, Hatogai, Iimura, et al., 2018; Kitaoka, Hatogai, Ochiai, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%